Two Biographies of Martin Luther - Platner, John Winthrop (Harvard theological review, 1912)
Luther is a fascinating subject for the historian. Not only does the personality of the man himself offer exceptional attractions, but so too does the age in which he lived, for then society, politics, and religion were all in the melting-pot, out of which in time was to issue the modern world. Luther was a product of the old, but he was also in a very true sense the exponent of the new. “The world is not what it once was,” said he to the German nobles,—knowing that again the fulness of the times had come. The favorite assertion of many German writers that Luther was the Reformation is often disputed, yet the statement is not half so exaggerated as it sounds, for if ever the spirit of a great movement which permanently affected the welfare of mankind got itself embodied in the person of one man, that movement was the Protestant revolution, and that man was Friar Martin.